Biochemical and physicochemical characterization of traditional rice wine of nyishi tribe of Arunachal Pradesh, India - Sony Kumari; Tarh Ama
Rice wine is a traditional alcoholic beverage of the Nyishi tribe of Arunachal Pradesh, prepared using 'Opo,' a traditional starter culture passed down through generations. This study investigates the biochemical significance of different rice wine varieties, focusing on their mineral content, bioactive components, and physicochemical properties. Mineral analysis revealed the presence of essential elements such as iron (Fe), calcium (Ca), zinc (Zn), and potassium (K). Among the studied varieties, Tisar wine exhibited the highest acceptability score, pH, alcohol content, and carbohydrate concentration, while Kecha wine was notable for its high protein, phenolic, and flavonoid contents. Bioactive compound analysis identified ga(B-D-glucopyranoside in Adak wine and hexadecanoic acid in other varieties as the predominant components, contributing to the wines' potential health benefits. These findings provide valuable insights into the physicochemical and biochemical properties of traditional rice wine, highlighting its significance in indigenous practices and potential applications in functional foods.s